Evaluation of Shugor, Dubasi and Watish subtypes of Sudan Desert sheep at the El-Huda National Sheep Research Station, Gezira Province, Sudan - Sulieman, A.H.; Sayers, A.R.; Wilson, R.T. (International Livestock Centre for Africa, 1990)
Presents results obtained from a trial conducted at El-Huda National Sheep Research Station, Sudan, Shugor, Dubasi and Watish subtypes of Sudan Desert sheep to compare productivity, reproductivity and animal performance, with particular reference to lambing, lambing intervals, body weight, growth rates and mortality rates, incl. recommendations for further investigations.